Effect of Ibicella lutea on uropathogenic Proteus mirabilis growth, virulence, and biofilm formation - Vanessa Sosa; Pablo Zunino (Journal of Infection in Developing Countries)
Background: Proteus mirabilis, an important uropathogen that can cause complicated urinary tract infections (UTI), has emerged as a therapeutic problem following mutations that compromise the use of antimicrobial drugs. Due to the serious effects associated with uropathogenic P. mirabilis and the problems related to the use of antibiotics, it is necessary to develop alternative strategies for its control. The objective of this study was to assess the effect of Ibicella lutea extract, a South American indigenous plant, on growth, virulence and biofilm production of uropathogenic P. mirabilis.